2000
DOI: 10.1902/jop.2000.71.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Biodegradable Chlorhexidine Chip in the Treatment of Adult Periodontitis: Clinical and Radiographic Findings

Abstract: These data indicate that the CHX chip, when used as an adjunct to scaling and root planing, significantly reduces loss of alveolar bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
2
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 12 publications
7
35
2
2
Order By: Relevance
“…Regarding adjunctive local (SRPloc) therapy, irrigation of the pockets with disinfectants, application of local drug delivering devices [17][18][19][20][21][22] or local laser treatment [23][24][25][26] were identified. Pocket irrigation and mouth rinses in most of the studies were performed with chlorhexidine [27][28][29]66].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding adjunctive local (SRPloc) therapy, irrigation of the pockets with disinfectants, application of local drug delivering devices [17][18][19][20][21][22] or local laser treatment [23][24][25][26] were identified. Pocket irrigation and mouth rinses in most of the studies were performed with chlorhexidine [27][28][29]66].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies assessing local antibiotic/antiseptic treatment ( Figure 1) [20,24] as well as three studies with a systemic antimicrobial approach Figure 2) [40, 41,43] showed relatively high values for standardized mean differences in pocket reduction. This can be explained as follows: some of these studies included high numbers (up to 190) of participants [68] and/or had a small spread i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In its present formulation, the chip resorbs and releases chlorhexidine in the pocket for approximately 7 to 10 days following placement. The average CHX concentration remain above 150 ppm at least 7 days (18). Polytetrafluoroethylene (PTFE) nonporous membrane (Tecnoflon-Brasflon, Ind.…”
Section: -Microscopic Analysismentioning
confidence: 99%